2021
DOI: 10.15244/pjoes/134640
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Three-Field Crop Rotation System and Cereal Monoculture on Grain Yield and Quality and the Economic Efficiency of Durum Wheat Production

Abstract: IntroductionReduced tillage and no-tillage systems are a domain of present-day agriculture [1][2][3]. This is due to production and economic respects, while the grain yield obtained from such systems is only slightly lower than that obtained from cost-consuming conventional tillage [4][5][6][7]. Hernanz et al. [8] demonstrated that the energy efficiency of wheat cultivation is higher under no-tillage than under reduced and conventional tillage systems. Unfortunately, such solutions also have many drawbacks. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…In general, the use of different crop rotations in our experiment generated production differences in durum wheat, highlighting the use of the legume (bean) as a pre-crop, which has been reported by several authors [3][4][5]30,32 . The incorporation of different levels of residues in our experiment had no effect on the production of durum wheat, different from papers of this and other plant species 4,[33][34] .…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…In general, the use of different crop rotations in our experiment generated production differences in durum wheat, highlighting the use of the legume (bean) as a pre-crop, which has been reported by several authors [3][4][5]30,32 . The incorporation of different levels of residues in our experiment had no effect on the production of durum wheat, different from papers of this and other plant species 4,[33][34] .…”
Section: Discussionsupporting
confidence: 70%
“…The effect of bean as a pre-crop on grain yield compared to canola can be explained by the benefits of legumes on the contribution to the soil of compounds of lower molecular weight that contribute to increase the microbial biomass [25][26][27][28] , as well as for the contribution of nutrients for the following crop [29][30][31] . In the case of durum wheat, Woźniak et al 3 also reported a positive effect of including a legume in the rotation (pea crop), with a 37% increase in yield compared to rotations with only cereals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations